Anticarcinogenic potentials of tea catechins - Li, Xiao-Xiang; Liu, Chang; Dong, Shu-Ling; Ou, Can-Song; Lu, Jian-Liang; Ye, Jian-Hui; Liang, Yue-Rong; Zheng, Xin-Qiang (Frontiers in Nutrition, 2022)
Catechins are a cluster of polyphenolic bioactive components in green tea. Anticarcinogenic ef-fects of tea catechins have been reported since the 1980s, but it has been controversial. The pre-sent paper reviews the advances in studies on the anticarcinogenic activities of tea and catechins, including epidemiological evidence and anticarcinogenic mechanism. Tea catechins showed an-tagonistic effects on many cancers, such as gynecological cancers, digestive tract cancers, incident glioma, liver and gallbladder cancers, lung cancer, etc. The mechanism underlying the anti-carcinogenic effects of catechins involves in inhibiting the proliferation and growth of can-cer cells, scavenging free radicals, suppressing metastasis of cancer cells, improving im-munity, interacting with other anticancer drugs, and regulating signaling pathways. The inconsistent results and their causes are also discussed in this paper.